2021
DOI: 10.1177/2473974x211018612
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Technology Use Among Patients With Head and Neck Cancer and Implications for Telehealth

Abstract: Objective To describe baseline technology use within the head and neck cancer (HNC) population prior to the COVID-19 pandemic. Study Design Cross-sectional analysis of National Health Interview Survey (NHIS) data. Setting The NHIS is a survey of population health administered in person annually to a nationally representative sample of noninstitutionalized US residents via a complex clustered sampling design. Methods Data regarding technology use, cancer history, and demographics were extracted from the NHIS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The majority of participants had access to a device that allowed them to attend their telehealth appointments, with a minority requiring support to use this. This indicates that although studies have shown HNC patients to be less likely to use general technology (Warinner et al., 2021), this patient group is able to access telehealth appointments and therefore should be offered this option as part of their care pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of participants had access to a device that allowed them to attend their telehealth appointments, with a minority requiring support to use this. This indicates that although studies have shown HNC patients to be less likely to use general technology (Warinner et al., 2021), this patient group is able to access telehealth appointments and therefore should be offered this option as part of their care pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Warinner et al. (2021) explored baseline technology use within the HNC population before the COVID‐19 pandemic. They found that this patient group were less likely to use general technology (computers, internet or email) when compared with other patients with cancer, although this difference was not statistically significant.…”
Section: Background and Aimsmentioning
confidence: 99%
“…If not proactively addressed, these disparities may preclude equitable access to teleneurology services across diverse populations and potentially exacerbate pre-existing health care inequalities, particularly among underserved minority populations, elderly patients, and patients with low health literacy or digital literacy. 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 It is estimated that over one in four Americans lack access to requisite technologies or digital literacy to engage in telemedicine visits, raising concerns that patients who are most vulnerable and in need of enhanced health care access may be the ones who are least likely to benefit from the advent of telemedicine technologies. 90 These issues are further magnified in considering access to teleneurology in less developed countries.…”
Section: Justice and Equity In Teleneurologymentioning
confidence: 99%
“…Increasingly, patients are looking to the internet for information, exploring it in their own time and at their own pace (2). Additionally, the current global pandemic has illustrated how technology can be used to support patients through virtual clinics, technology apps, and obtaining pre-and posttreatment information online (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%